Personal Reputation Among Fine Arts Students (Architecture Image Studies, 2026)
This study assessed the level of personal reputation among undergraduates in the College of Fine Arts, University of Baghdad. Guided by Reputation Enhancement Theory, we administered a validated 26-item Personal-Reputation Scale to a stratified random sample of 400 students drawn equally from four academic departments and four study years. The mean reputation score (M = 98.51, SD = 12.20) was significantly higher than the theoretical midpoint of 78, t(399) = 33.61, p < .001, indicating an overall favourable reputational standing. A 2 × 4 factorial ANOVA revealed no significant main effects of gender or study year and no interaction effect, suggesting reputational consistency across demographic groups. These results highlight the salience of reputation as a shared cultural construct within fine-arts education and point to the value of reputation-supportive policies that reinforce positive self-presentation and collegial norms.